Business Intelligence and Human Resource Management Concept, Cases, and Practical Applications. - Singh, Deepmala; Singh, Anurag; Omar, Amizan; Goyal, S. B. (Milton : Productivity Press, 2022)
Business Intelligence (BI) is a solution to modern business problems. This book discusses the relationship between BI and Human Resource Management (HRM). In addition,it discusses how BI can be used as a strategic decision-making tool for the sustainable growth of an organization or business. BI helps organizations generate interactive reports with clear and reliable data for making numerous business decisions. This book covers topics spanning the important areas of BI in the context of HRM. It gives an overview of the aspects, tools, and techniques of BI and how it can assist HRM in creating a successful future for organizations. Some of the tools and techniques discussed in the book are analysis, data preparation, BI-testing, implementation, and optimization on GR and management disciplines. It will include a chapter on text mining as well as a section of case studies for practical use. This book will be useful for business professionals, including but not limited to, HR professionals, and budding business students.
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: BUSINESS & ECONOMICS / Production & Operations Management; BUSINESS & ECONOMICS / Management; Personnel management; Business intelligence